2021
DOI: 10.1002/jcla.23704
|View full text |Cite
|
Sign up to set email alerts
|

Changes and significance of plasma fibrinogen gamma‐chain concentration in preeclampsia patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Duan et al found that fibrinogen in mild preeclampsia patients was not less than in controls, and fibrinogen in severe preeclampsia patients was significantly higher than in controls [ 3 ]. Another research demonstrated that at the gestational age of 32 weeks, the plasma fibrinogen γ chain levels in preeclampsia patients were significantly elevated [ 13 ]. However, Chen and her colleagues concluded that the fibrinogen concentration in preeclampsia patients was significantly lower than in healthy pregnant women (1.59 ± 1.07 versus 4.19 ± 0.63, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Duan et al found that fibrinogen in mild preeclampsia patients was not less than in controls, and fibrinogen in severe preeclampsia patients was significantly higher than in controls [ 3 ]. Another research demonstrated that at the gestational age of 32 weeks, the plasma fibrinogen γ chain levels in preeclampsia patients were significantly elevated [ 13 ]. However, Chen and her colleagues concluded that the fibrinogen concentration in preeclampsia patients was significantly lower than in healthy pregnant women (1.59 ± 1.07 versus 4.19 ± 0.63, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%